SURGICAL SITE INFECTIONS AND WOUND DISRUPTION IN SKIN CLOSURE WITH STAPLES VERSUS ABSORBABLE SUBCUTICULAR SUTURES IN CESAREAN SECTIONS: A COMPARATIVE STUDY - MAHMOOD, T; MUSTAFA, MA; AMIN, J; TAHIR, E; ZULFIQAR, MA; MOAZZAM, MSU (Biological and Clinical Sciences Research Journal, 2024)
Cesarean sections are among the most common surgical procedures globally, and optimal skin closure methods are critical for minimizing postoperative complications. This study evaluates the incidence of surgical site infections (SSIs) and wound disruptions and compares postoperative outcomes between skin closure with metallic staples and absorbable subcuticular sutures in cesarean deliveries Objective: To compare surgical site infections and wound disruptions in skin closure with staples vs absorbable subcuticular sutures in patients undergoing cesarean sections. Methodology: A prospective study was conducted in the Surgery and Gynecology Department of Jinnah Hospital, Lahore from August 2023 to August 2024. A total of 100 pregnant women with a gestation age of 24 weeks or more undergoing c-sections were selected for the study. Patients were divided into Group A (n=50) with women undergoing skin closure with metallic staples and Group B (n=50) with women undergoing skin closure with 4-0 Monocryl sutures. All patients were examined at discharge and 4-6 weeks postpartum. The primary endpoint was postpartum surgical site infection or wound disruption. The second endpoints were postoperative and postpartum pain score, surgery duration, cosmesis score and patient satisfaction. Results: At discharge, the primary outcome was 8% in group A and 1% in group B (RR: 13.2 (2.2-100), p<0.001). At follow-up, the primary outcome was 15% in group A and 5.8% in group B (2.7 (1.5-4.8), p=0.010). The average duration of surgery was longer in group B (60 vs 50 minutes). Both groups did not differ significantly in pain scores, satisfaction scores, and cosmesis scores. Conclusion: High incidence of surgical site infections and wound disruption were noted in skin closure with staples as compared to sutures in women undergoing cesarean delivery. However, both methods were similar in pain scores, cosmesis scores, and patient satisfaction.